Antiviral activity of Micrococcus luteus against the infection of bean yellow mosaic virus in faba bean - Elsharkawy, Mohsen Mohamed; Alzahrani, Faisal Ay (Frontiers in Plant Science, 2026)
IntroductionPlant viruses severely affect agricultural crops and are the cause of almost half of all major plant diseases. No successful antiviral agents are now widely available for agricultural use against phytoviruses. MethodsMicrococcus luteus was collected from the rhizosphere of faba bean and molecularly characterized via the 16S rRNA (Acc# PV650302). Soil inoculation greatly enhanced growth and induced systemic resistance to BYMV (Bean yellow mosaic virus) infection in faba bean plants grown in the greenhouse or field conditions.Results and DiscussionSoil drenching application of Micrococcus luteus resulted in a 78% decrease in the severity of the disease and a 70% decrease in viral accumulation levels. Superoxide dismutase (SOD), total chlorophyll content, antioxidant enzymes like catalase (CAT), ascorbate peroxidase (APX), and polyphenol oxidase (PPO) were all significantly increased after M. luteus treatment. The levels of oxidative stress indicators, such as malondialdehyde (MDA) and hydrogen peroxide (H2O2), were shown to be much lower after M. luteus treatment. The transcripts of genes involved in pathogenesis were found to be upregulated with these alterations. It is possible to use M. luteus as a biocontrol agent, which is a practical and environmentally friendly way to protect faba bean plants against BYMV infection, since it may increase faba bean growth and generate systemic resistance against BYMV disease. Antiviral action against viral infections in plants has never been previously documented for M. luteus.